Linux Firewalls - Ziegler, Robert L. (New Riders, 2000)
An Internet-connected Linux machine is in a high-risk situation. Linux Firewalls, Third Edition details security steps that any sized implementation--from home use to enterprise level--might take to protect itself from potential remote attackers. As with the first two editions, this book is especially useful for its explanations of iptables, packet filtering, and firewall optimization along with some advanced concepts including customizing the Linux kernel to enhance security.The third edition, while distribution neutral, has been updated for the current Linux Kernel and provides code examples for Red Hat, SUSE, and Debian implementations. Don't miss out on the third edition of the critically acclaimed Linux Firewalls.